(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article talks about the role of the text in teaching Russian as a foreign language, the value of which is not only a comprehensive communication unit of second language learning, but also as the main didactic units that can detect and display text potency of its constituent formal linguistic units. The material in this article reflects the professional direction of teaching different types of reading when working with text. The development of speech activity in the future professionals in the field of language specialization is based on the selection of scientific texts and analysis, including various types of reading, consisting of such milestones as the perception, analysis, reproduction and production. Also the author of the article suggests fragments of training sessions on the Russian language, intended for physics students and aimed at the assimilation of specific features of scientific style with access to productive speech, based on the activity approach. These instructional techniques will help improve future specialist linguistic and communicative competence on the basis of scientific style, language specialty.